The contribution of amino acids to the odour of a prey species in the Senegalese sole (Solea senegalensis). - Barata, Eduardo N. (2008)
For many fish, olfaction is important in food search and consumption. Amino acids are known to elicit feeding behaviour in several species. The aim of the current study was to evaluate the contribution of amino acids to the odour of a natural prey organism of the Senegalese sole (Solea senegalensis). Both whole-body macerates and substances released to the water by living ragworms (Hediste diversicolor) were fractionated by molecular weight filtration followed by solid-phase extraction (SPE), and the olfactory activity of the resultant fractions was assessed by the electro-olfactogram (EOG) in the sole. The amino acid concentrations of the macerate and water were determined by gas chromatography and mass spectrometry (GC–MS). In the macerate, the majority of odorants were small molecular weight compounds (b500 Da) which were not retained by C-18 SPE cartridges. An artificial mixture of amino acids at the same concentrations as found in the macerate had similar olfactory potency. The odorants released to the water by living ragworms were also small molecular weight compounds (b500 Da) but the majority of olfactory activity could be extracted by C-18 SPE cartridges. The concentrations of amino acids in these samples were too low to contribute greatly to its olfactory potency. These results suggest that, whilst olfactory sensitivity to amino acids may explain most of the potency of the macerate, living ragworms are releasing additional odorants other than amino acids which may be equally important in chemosensory food location in the sole.